(untitled) (Indian Journal of Arid Horticulture, 2017)
In the present investigation, the response of bottle gourd to different levels of vermicompost (control, 3, 6 and 9 tones ha- 1) and nitrogen (control, 50, 75 and 100 kg ha-1) was studied at SKRAU, Bikaner during summer season of 2016. The vermicompost applied at the rate of 6 tones ha-1 has shown least number of days for appearance of first female flower, while number of primary branches per vine, length of leaf ( cm), per cent fruit set, fruit length, weight and total yield per vine etc. were found maximum in plants applied with 9 tones ha- 1• The application of increasing levels of nitrogen 100 kg ha- 1has significantly increased the length of leaf, per cent fruit set, number of fruits per vine, fruit length, weight and total yield per vine etc., chlorophyll content in plant (mg/100), P uptake by plant and available N content in soil after harvesting compared to the control. The treatment combination of vermicompost (9 t ha- 1) + nitrogen (100 kg ha- 1) has showed maximum number of primary branches per vine, leaf length (cm), per cent fruit set, number of fruits per vine etc. compared to the control plants. The maximum yield (q ha- 1) was found under the treatment combination of vermicompost (9 t ha- 1) + nitrogen (100 kg ha- 1) while remaining treatment combinations was at par with each other. The higher nitrogen content as well as B: C ratio (l.70) in plant was observed in the treatment combination of vermicompost (6 t ha- 1) + nitrogen (100 kg ha- 1).